Progressive radiosity method on clusters using a new clipping algorithm. (8th August 2005) - Amor, M.; Sanjurjo, J.R.; Padron, E.J.; Doallo, R.
Global illumination simulation is highly critical for realistic image synthesis; without it, the rendered images look flat and synthetic. The main problem is that the simulation for large scenes is a high time-consuming process. In this paper, we present a uniform partitioning method in order to split the scene domain into a set of disjoint subspaces which are distributed among the processors of a distributed memory system. Since polygons partially inside several subspaces have to be clipped, we have developed a new clipping algorithm to manage this situation. Memory and communication requirements have been minimised in the parallel implementation. Finally, in order to evaluate the proposed method, we have used a progressive radiosity algorithm, running on two different PC clusters with modern processors and network technologies as a testbed. Good results in terms of speedup have been obtained.